Los efectos de la música en el libro VI del ‘De Musica’ de Agustín - Caruana, Salvino (Avgvstinvs, 2023)
The article deals with Augustine’s De Musica, first of all highlighting the structure of the Work, and then focusing on Book VI, stressing its main themes. A presentation is made of the main texts in Augustine’s works in which music is discussed. Subsequently, the presence of the hymn Deus creator Omnia in the work of St. Augustine is explored.